Analysis of Spirituality and Spiritual Care Perception of Students at Faculties of Health Sciences - Es, Muhsine; Eti Aslan, Fatma; Çınar, Fadime (Innovative Journals, 2020)
Aim: This study was designed to analyze the perception of spirituality and spiritual support of students studying at faculties of health sciences. Materials and Methodology: This descriptive study population was collected of 1382 students receiving education at the departments of Nutrition and Dietetics, Pediatric Development, Physical Therapy and Rehabilitation and Nursing and Health Management of a Foundation University. Sampling method was not preferred in this research but students who agreed to take part in the study were included within its scope. Data was collected between January 3-8, 2018 and the research was completed with 857 students. In addition, relevant data was collected by means of “Individual Information Form” and “Spirituality and Spiritual Care Rating Scale”. SPPS 24.0 statistical package software was used in the assessment of the data. Findings: It was determined that 37.7% of the students participating in the research study are in the Department of Nutrition and Dietetics, 23% are 20 years old and 84.7% are female. It was further determined that 27.4% are juniors, 77.2% did not receive any education on spirituality and the majority of those who did found the education on spirituality sufficient. The total mean score of all students was determined as 53,60 ± 9,58 as a result of the “Spirituality and Spiritual Rating Care Scale” evaluations in the study. There was no statistically significant difference (p>0.05) between the mean score of the students according to their departments and age variable. On the other hand, there was a statistically significant difference (p<0.05) between the mean scale scores of the freshmen and senior students in their departments. In addition, there was a statistically significant difference (p<0.05) between the mean scale scores of the students who received education on spirituality and those who did not. Conclusion: the study reveals that students have an above average understanding of spirituality and spiritual care, but do not receive sufficient education on the subject. Therefore, there is a need for a higher level of education in this area. It is recommended that educational institutions provide classes on spiritual care so that students fill the gap in their knowledge.
Keywords: Spirituality; Spiritual care; Health; Health sciences students